Addressing the Ethical Issues Associated with Fieldwork Education in Occupational Therapy: Results of an Empirical Study Conducted in Quebec - Drolet, Marie-Josée; Baril, Nancy; Sauvageau, Anick; Renaud, Sandrine (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2020)
Occupational therapists who contribute to fieldwork education are exposed to ethical issues when supervising trainees. Both the ethical issues and the solutions to address these ethical issues are undocumented in the literature. A qualitative study was conducted to document these issues and their solutions. Twenty-three occupational therapists with supervising experience participated in this study. All the participants reported experiencing ethical issues while supervising trainees. This article aims to present the solutions proposed by the participants in order to address the ethical issues of fieldwork education. Intrinsic solutions are linked to supervisors’ ethical, pedagogical or occupational therapy competences. The extrinsic solutions deal with the appropriate measures which can and should be implemented so as to better support the supervisors’ work and better recognize the important contribution of occupational therapists who train the next generation of occupational therapists in clinical settings. This study is likely to have implications on clinical practice, teaching, research and governance.